2019
DOI: 10.2139/ssrn.3412517
|View full text |Cite
|
Sign up to set email alerts
|

Moderating Effect of the Use of eWOM on Subjective Norms, Behavioural Control and Religious Tourist Revisit Intention

Abstract: Moderating effect of the use of eWOM on subjective norms, Moderating effect of the use of eWOM on subjective norms, behavioural control and religious tourist revisit intention behavioural control and religious tourist revisit intention

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…In this study, tourism experience trumps media reviews and substance. eWOM was insignificant in past research such as Sirichareechai et al (2018) and Iriobe et al (2019). These scholars' findings concluded in their investigations that eWOM was ineffective for traveling decision-making for two main reasons.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In this study, tourism experience trumps media reviews and substance. eWOM was insignificant in past research such as Sirichareechai et al (2018) and Iriobe et al (2019). These scholars' findings concluded in their investigations that eWOM was ineffective for traveling decision-making for two main reasons.…”
Section: Discussionmentioning
confidence: 85%
“…Online reviews affect how tourists act and plan to act (Oday et al, 2021), but eWOM readers must evaluate them (Verma & Dewani, 2021). Iriobe et al (2019) found that eWOM did not affect tourists' intention to revisit Nigerian religious destinations. The findings suggested that information from reliable sources or authorities may be required to influence tourists to visit faith-based destinations.…”
Section: Ewom As a Mediator Rolementioning
confidence: 95%
“…Tourists’ intentions of revisiting a festival will positively influence if the acquaintance is essential to them and provides positive support for visiting festivals (Choo et al, 2016). Iriobe and Abiola-Oke (2019) emphasized that the collective impact of eWOM, subjective norm, and attitude strongly influences religious tourists’ RI. Similarly, few other studies found a positive impact of SN on tourist visit/RI (Hasan et al, 2020; Jalilvand et al, 2012; Park et al, 2017; Soliman, 2019).…”
Section: Theoretical Framework and Hypothesis Formulationmentioning
confidence: 99%
“…Based on the study the use of eWOM has a relationship or effect to tourist revisiting intention to a religious destination. Moreover, the use of other promotional tool is useful to attract new visitors (Iriobe et al, 2019).…”
Section: International Journal Of Research Studies In Managementmentioning
confidence: 99%